PERKEMBANGAN STRUCTURAL EQUATION MODELING (SEM) DAN APLIKASINYA DALAM BIDANG EKONOMI - Sayyida, Sayyida; Alwiyah, Alwiyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
Economic phenomenon Area is complicated to be researched. Many researchwhich is difficult to be finished by ordinary analysis. So that in the year 1916, SwallWright introduce analyzer of Structural Equation Modelling (SEM). Until this time SEMis popular among social research of do not aside in economic area. Have many successeconomics research finish economic phenomenon with structure SEM analyse whichcomplicated. Structure in SEM which is complicated oblige all consumer to be more takea care in using it in order not to happened mistake of interpretation particularly againmistake of usage. This article aim to give the understanding of hitting SEM and its growthand also its application specially to researcher in economic area. This article present theunderstanding of hitting SEM started from estimation method, software which can wear,way of activity, weakness and advantage and also various application of SEM ineconomic area specially.